1970
DOI: 10.1002/1097-0142(197002)25:2<450::aid-cncr2820250224>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with local chemotherapy and immunotherapy in premalignant and malignant skin lesions

Abstract: Local chemotherapy with 5‐FU was investigated in premalignant and superficial malignant skin lesions in more than 700 patients. Resolution of neoplasms occurred in more than 95% of patients and lasted for observation periods of up to 6 years. Healing took place without perceptible scarring and with restoration of normal color and texture of the skin. Local side effects were minor. Systemic toxicity did not occur. Several agents, with and without cystostatic activities, produce immune reactions which are more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
3

Year Published

1971
1971
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 12 publications
(6 reference statements)
0
19
0
3
Order By: Relevance
“…5-FU is a chemotherapeutic agent with modest activity as such when given for therapy of cancer of internal organs. Topically, it has been effective in preventing the progression of actinic keratoses of the skin to cancer in humans (18). It has also produced chemoprevention of benzo(␣)pyrene-induced epidermal carcinogenesis in the mouse (19).…”
Section: Discussionmentioning
confidence: 99%
“…5-FU is a chemotherapeutic agent with modest activity as such when given for therapy of cancer of internal organs. Topically, it has been effective in preventing the progression of actinic keratoses of the skin to cancer in humans (18). It has also produced chemoprevention of benzo(␣)pyrene-induced epidermal carcinogenesis in the mouse (19).…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be demonstrated that the factors from the ascites fluid are the same as those released in vitro from the activated macrophage. In addition, recent studies have demonstrated that nonspecific target cell destruction can occur in viva in cutaneous delayed hypersensiti~rity reactions (24,25). The main effector cell in these reactions appears to be a monocytic ceI1.…”
Section: Discussionmentioning
confidence: 99%
“…BERTON ZBAR TOMIKO TANAKA* Cellular Immunity Section, Biology Branch, National Cancer Institute, Bethesda, Maryland 20014 Previous studies of response characteristics to physiological stimulation of single cells in the somatosensory system (1)(2)(3)(4)(5)(6) have not suggested an organizational hierarchy analogous to that demonstrated by Hubel and Wiesel (7) in the visual system. Indeed, Powell and Mountcastle (1) emphasize the fidelity with which response properties of peripheral somesthetic receptors are reproduced by single units in the somatosensory thalamic relay nucleus (VPL) and primary cortical receiving area, Sl (Brodmann's cytoarchitectonic areas 3, 1, and 2).…”
mentioning
confidence: 99%
“…Immunologic methods are of value in the clinical treatment of epidermal tumors, intradermal metastases of malignant melanoma, and acute leukemia (1). Successful treatment of skin tumors in man requires the development of an inflammatory reaction of the delayed type at the site of the tumor.…”
mentioning
confidence: 99%